The Influence of Push and Pull Factors of Tourism on Decision-Making and Behavior of Domestic Tourists in Batu City, East Java - Rahman, A. Faidlal; Mufarrohah, Mufarrohah (E-Journal of Tourism; Volume 12 Number 1 (March 2025)DO - 10.24922/eot.v12i1.124670, 2025)
Batu City, known for its diverse tourist attractions and supporting facilities, has become a favored destination for domestic tourists. Visitor motivations vary, influenced by internal (push) and external (pull) factors that affect their decision-making and travel behavior. This study applied a quantitative approach to examine the influence of push and pull motivational factors on tourist decision-making and behavior. A total of 100 domestic tourists were selected through accidental sampling, and data were collected using closed-ended questionnaires with a Likert scale. Analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0. The findings revealed that: (1) Push factors significantly influenced tourist decision-making (p = 0.003); (2) Pull factors also significantly influenced tourist decision-making (p = 0.000); and (3) Tourist decision-making significantly affected tourist behavior (p = 0.000). These results suggest that the Batu City Government should continue enhancing the quality and uniqueness of its attractions, diversifying tourism products, and improving visitor facilities to strengthen its appeal to domestic tourists and support sustainable tourism development.